Use of a smartphone application as a treatment and follow-up for tobacco use disorder: a case report - Yararbaş, Görkem; Akyel, Betül (Journal of Dependence, 2017)
Objective: The objective of this study is to investigate the effect of a smartphone health application in a tobacco use disorder case.Method: SmokeBeat smartphone application was used in conjunction with a smartwatch. A tobacco use disorder case used the application for five months. Additionally, the case was evaluated with Fagerstrom Test for Nicotine Dependence (FTND), Autonomy Over Tobacco Scale (AUTOS) and Carbon Monoxide levels in breath initially and finally.Results: The analysis shows that after using the application for five months, daily number of cigarettes, CO levels and dependency scores were on the decline.Conclusion: This case is an important example for using a smartphone application in order to reduce the number of cigarettes, supporting smoking cessation and behavioral change. It is thought to be useful for cases who are not suitable for pharmacotheraphy or without motivation.
Keywords: Healthcare software; Tobacco Use Disorder; harm reduction